Examining the Cross-Border Acquisition Strategy of Chinese Companies: The Moderating Roles of State Ownership and Institutional Transition. (November 2013) - Li, Jiatao; Xie, Zhenzhen
This study investigates how information asymmetry influences the equity shares acquired in cross-border acquisitions by Chinese firms. Taking an institution-based perspective, we propose that the extent to which Chinese acquirers react to information asymmetry in the way as predicted by economic perspectives will be influenced by the home institutions of these emerging market multinational enterprises. Based on 547 cross-border acquisitions made by Chinese acquirers from 1987 to 2007, the findings show that Chinese state-owned acquirers were less committed to an economic logic than non-state-owned acquirers. The institutional transition taking place in China in recent years has increased the importance of economic drivers for the Chinese acquirers.